National Institutes of Health Toolbox Emotion Battery for English- and Spanish-speaking adults: normative data and factor-based summary scores - Babakhanyan I (Patient Related Outcome Measures, 2018)
Ida Babakhanyan,1,2 Benjamin S McKenna,2 Kaitlin B Casaletto,3 Cindy J Nowinski,4 Robert K Heaton2 1Defense and Veteran’s Brain Injury Center, Camp Pendleton, 2Department of Psychiatry, University of California, San Diego, La Jolla, 3Department of Neurology, University of California, San Francisco, San Francisco, CA, 4Department of Medical Social Sciences, Northwestern University, Chicago, IL, USA Background: The National Institutes of Health Toolbox Emotion Battery (NIHTB-EB) is a “common currency”, computerized assessment developed to measure the full spectrum of emotional health. Though comprehensive, the NIHTB-EB’s 17 scales may be unwieldy for users aiming to capture more global indices of emotional functioning. Methods: NIHTB-EB was administered to 1,036 English-speaking and 408 Spanish-speaking adults as a part of the NIH Toolbox norming project. We examined the factor structure of the NIHTB-EB in English- and Spanish-speaking adults and developed factor analysis-based summary scores. Census-weighted norms were presented for English speakers, and sample-weighted norms were presented for Spanish speakers. Results: Exploratory factor analysis for both English- and Spanish-speaking cohorts resulted in the same 3-factor solution: 1) negative affect, 2) social satisfaction, and 3) psychological well-being. Confirmatory factor analysis supported similar factor structures for English- and Spanish-speaking cohorts. Model fit indices fell within the acceptable/good range, and our final solution was optimal compared to other solutions. Conclusion: Summary scores based upon the normative samples appear to be psychometrically supported and should be applied to clinical samples to further validate the factor structures and investigate rates of problematic emotions in medical and psychiatric populations. Keywords: emotional functioning, NIH Toolbox Emotion Battery, factor analyses, summary scores, normative data